PHYTOCHEMISTRY AND BIOLOGICAL ACTIVITIES OF CRATEVA ADANSONII EXTRACTS - Nounagnon, Martial S.; Dah-nouvlessounon, Durand; NTCHA, Christine; Legba, Boris; Baba-moussa, Farid; Adjanohoun, Adolphe; Baba-moussa, Lamine (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: This study aims to search the secondary metabolites of Crateva adansonii (leaves and bark) and evaluate some biological activities (antimicrobial, antioxidant and cytotoxicity's property) of these extracts. Methods: The phytochemical screening was made with standard method. Agar diffusion method was used for antibacterial activity coupled with Minimum Inhibitory Concentration (MIC) and Bactericidal (MBC) determination. The antifungal test was performed by the mycelial development reduction method. DPPH method was used to evaluate the extracts antioxidant activity. Artemia salina larvae were use as support to evaluate the toxicity of the extracts. Results: The results of the phytochemical screening reveal the presence of polyphenols, triterpenoids, and glycosides in the both organs (leaves and bark) of C. adansonii. All the extracts have low activity on the reference strains with a larger diameter of 17±00 mm (S. oralis). Only the ethanolic and hydroethanolic leaf's extracts inhibited respectively 20% and 10%, of the clinical strain S. aureus. The ethyl acetate leaf's extract shows the best antifungal activity (89,19%) with A. clavatus. All extracts present dose-dependent antiradical properties and are non-toxic for the cells of Artemia salina. C. adansonii bark extracts had the best reducing power (23,80±0, 137 mmol/g EqAA EAA) of the DPPH radical. Conclusion: C. adansonii is therefore an active principle source for the development of drugs to antimicrobial and antioxidant activities